Data-Driven Research on the Matching Degree of Eyes, Eyebrows and Face Shapes - Zhao, Jian; Zhang, Meng; He, Chen; Zuo, Kainan (Frontiers in Psychology, 2019)
There is a close relationship between the attractiveness of the face and the facial features. The shape and proportion of the five sense organs determine the level of attractiveness, in which the eyes and eyebrows are particularly vital. In this paper, we propose a method to study the facial attractiveness by combining global face shape and local geometric features of eye and eyebrow and using computer big data analysis for assistant. Firstly, we collect 300 images of East Asian female and use machine learning methods to evaluate the attractiveness scores of face images. Secondly, geometric models are constructed separately for the eyebrows and the eyes to obtain their geometric and shape features. Correlation analysis is performed on the obtained data to study their shape matching of different facial attractiveness rating levels. Finally, the relationship between the shape of face and eyebrows is analyzed by combining the facial ratio and the geometric features of the eyebrows. The research in this paper can provide reference for medical and beauty institutions and women's makeup, and further study on the field of facial aesthetic analysis based on geometric features.